From global workers to local entrepreneurs: Sri Lanka's former global factory workers in rural Sri Lanka - Hewamanne, Sandya (Third world quarterly, 2020)
Working in Sri Lanka's urban free trade zones (FTZs) introduces Sri Lanka's rural women to neoliberal ways of fashioning selves, which subsequently not only shape village entrepreneurial activities but also initiate negotiations in kinship, marriage, domestic arrangements, and community relations. The knowledges and networks that they develop while at the FTZ allow former workers to connect with global production networks as subcontractors, making them part of the cascading system of subcontracting that furthers the precarity of regular FTZ work. This article explores how these former workers manipulate varied forms of capital - social, cultural and monetary - to become local entrepreneurs and community leaders, while simultaneously initiating changes in rural social hierarchies and gender norms. When neoliberal economic restructuring manifests within local contexts it results in new articulations of what it is to be an entrepreneur and what it is to be a worthy, young, married woman. Overall, the paper sheds light on the fragmented and uneven manner in which neoliberal ethos take root in rural South Asia.